Management of acute venous thromboembolism in patients taking antiplatelet therapy. Issue 208 (December 2021) - Giraud, Marie; Catella, Judith; Cognet, Lucile; Helfer, Hélène; Accassat, Sandrine; Chapelle, Céline; Mismetti, Patrick; Laporte, Silvy; Mahé, Isabelle; Bertoletti, Laurent
Abstract: Background: Concomitant anticoagulant and antiplatelet therapy increases bleeding risk, but most data are derived from patients with atrial fibrillation. Patients with venous thromboembolism (VTE) may differ. Objective: To study the management of patients diagnosed with acute VTE while receiving antiplatelet treatment. The primary outcome was the number of patients discharged with concomitant therapy. Secondary outcomes were clinically relevant bleeding, cardiovascular events, recurrent VTE and death during follow-up, according to discharge therapy. Methods: We performed a post-hoc analysis of patients included in two prospective registries, sharing the same case report form, from 2007 to 2017. Results: Among the 1694 identified patients, 254 (15.0%) were receiving antiplatelet treatment at VTE diagnosis, of whom 61 (24.0%) were discharged with concomitant anticoagulant and antiplatelet therapy. In multivariable analysis, age ≥ 80 years-old and the use of Direct Oral Anticoagulants for VTE therapy were associated with the decision to stop the antiplatelet, while having dual anti-platelet therapy at baseline, a history of coronaropathy or peripheral arterial disease were associated with concomitant anticoagulant and antiplatelet therapy. The decision to stop antiplatelet was associated with a non-significant 46% decrease in the risk of bleeding (OR 0.54 (0.16; 1.78)), and a non-significant 68% increase in the risk of cardiovascular events (OR 1.68 (0.44; 6.46)). Conclusion: At acute VTE diagnosis, over 15% of patients were receiving antiplatelet agents, of whom 24% were discharged with concomitant anticoagulant and antiplatelet therapy. This therapeutic decision may be associated with a lower risk of cardiovascular events, but an increased risk of bleeding. Highlights: Concomitant anticoagulant and antiplatelet therapy (AP) increases the bleeding risk. A retrospective bicenter analysis of patients under AP at the time of VTE diagnosis. Advanced age and use of DOACs were associated with the decision of stopping AP. Dual AP and history of coronaropathy or PAD were associated with the decision of continuing AP. Stopping AP was associated with trends toward lower rates of bleeding, but higher rates of arterial events.